Sistem Operasional Prosedur Penanganan Klaim Kekurangan Muatan Dalam Asuransi Pengangkutan Kapal Laut PT. ASPAN Cabang Surabaya - Ramadhani, Rizky Amalia; Lazaro Prawirosastro, Carlos (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
PT. Aspan (Asuransi Purna Artanugraha) Branch Surabaya is a company engaged in the field of insurance services. There are several businesses in the offer by PT. Aspan Surabaya Branch, among others: Marine Hull Insurance, Cargo Insurance, Auto Insurance, Fire Insurance, Engineering Insurance (CAR & EAR), Personal Accident Insurance, Insurance Aircraft. The process begins with the issuance of the policy on charging SPPA by the insured party, which proceed to entry data from the SPPA to policy issuance request form. Handling claims in PT. Aspan Surabaya branch has its own capacity, if the claims submitted by the insured is not the capacity of the branch office in the proposed claims will be processed at the headquarters of PT. Aspan. Based on the discussion on the operational procedures in the cargo shortage claims handling cargo insurance of ships PT. Aspan Surabaya branch can be concluded as follows. The first one is the cause of the cargo shortage claims state of the charge current on the boat sailing from place of origin to destination. Second, document archiving policy insurance at PT. Aspan Surabaya Branch to facilitate evaluation of the document when the insured to make a cargo shortage claims. Third, employees of PT. Aspan Surabaya branch already working optimally so that the procedures for handling cargo shortage claims undone well and get good results.